A thousand words about microparticles in cardiology (Journal of Medical Science, 2014)
Microparticles (MPs) are membrane vesicles of 0.1–1 µm in diameter produced mainly by platelets, vascular endothelium and blood cells in response to cell activation and stress factors. MPs can be also released during malignant transformation or apoptosis. The essential step in MP formation is the loss of the cell membrane asymmetric phospholipid distribution as response to the increased intracellular calcium levels. MPs contain, proteins and genetic material (DNA, miRNA, mRNA) which enables them to interact and influence target cell. MPs are considered to be markers of ongoing pathophysiological processes in cardiovascular system, due to their role in inflammation and coagulation.